Selective Effect of Pesticides on Plant—A Review. Issue 1 (2nd January 2016) - Parween, Talat; Jan, Sumira; Mahmooduzzafar, Sumira; Fatma, Tasneem; Siddiqui, Zahid Hameed
Abstract : This review represents systematic and integrated picture of pesticide exposure to plant and its effect on growth and metabolism. Decades ago, agrochemicals were introduced aiming at enhancing crop yields and protecting crops from pests. Due to adaptation and resistance developed by pests to chemicals, every year higher amounts and new chemical compounds are used to protect crops, causing undesired side effects and raising the costs of food production. Biological chemical free agriculture is gaining also more and more support but it is still not able to respond to the need for producing massive amounts of food. The use of agrochemicals, including pesticides, remains a common practice especially in tropical regions and South countries. Cheap compounds, such as DDT, HCH, and Lindane, that are environmentally persistent, are today banned from agriculture use in developed countries, but remain popular in developing countries. As a consequence, persistent residues of these chemicals contaminate food and disperse in the environment. Therefore, the thrust of this paper was to review the application of pesticides effect early from germination to growth of the plant, leading to alteration in biochemical, physiological and different enzymatic and non-enzymatic antioxidants which ultimately affect the yield and resulted in residues in plant, vegetables, and fruits.